Africa’s climate leadership and health resilience: insights from the 2nd Africa Climate Summit, Addis Ababa, 2025 - Tahlil, Abdullahi Ahmed (Frontiers in Climate, 2025)
IntroductionThe 2nd Africa Climate Summit (ACS2), held in Addis Ababa, Ethiopia, in September 2025, marked a significant shift in Africa’s climate leadership, positioning the continent not only as a victim of climate change but also as a key solutions provider. Africa faces severe climate impacts despite contributing minimally to global greenhouse gas emissions, with consequences including health crises and economic losses. This paper explores the outcomes of ACS2 and the intersection of climate action and health resilience, outlining the continent’s commitments to renewable energy, climate finance, and nature-based solutions.MethodsThis study employs a policy review and analytical synthesis of official summit documents, including the Addis Ababa Declaration, technical reports, and expert session transcripts. Data was coded and analyzed across five key themes: climate finance, renewable energy, climate-health integration, nature-based solutions, and global climate diplomacy. The research also incorporates media briefings and partner reports to provide a comprehensive understanding of ACS2’s commitments and challenges.ResultsACS2 produced groundbreaking commitments, such as the launch of the African Climate Facility (ACF) to mobilize 50 billion annually for climate solutions and the integration of health resilience in climate policy. The Addis Ababa Declaration emphasized climate justice, linking development and climate action. Key initiatives, such as the Africa Green Industrialization Initiative and the African Forest Landscape Restoration Initiative, demonstrate Africa’s commitment to green industrialization and environmental restoration. The summit also prioritized renewable energy, setting ambitious targets for clean energy access and green growth.DiscussionWhile ACS2 marks a pivotal moment in Africa’s climate diplomacy, several implementation challenges remain, including financing gaps and institutional capacity constraints. Despite substantial financial pledges, Africa’s climate finance needs far exceed current commitments, and there are concerns regarding the adequacy of climate finance mechanisms. The paper discusses how ACS2’s outcomes align with Africa’s broader climate goals and offers policy recommendations for overcoming barriers to implementation. Additionally, it underscores the inseparability of climate justice and health resilience, stressing the importance of integrated solutions to both climate and health crises.